Insights into the Structure, Function, and Ion-Mediated Signaling Pathways Transduced by Plant Integrin-Linked Kinases - Popescu, Sorina C.; Brauer, Elizabeth K.; Dimlioglu, Gizem; Popescu, George V. (Frontiers in Plant Science, 2017)
Kinases facilitate detection of extracellular signals and set in motion cellular responses for plant adaptation and survival. Some of the energy utilized for kinase signal processing is produced through the activity of ion transporters. Additionally, the synergy between cellular ions and signal transduction influences plant response to pathogens, and their growth and development. In plants, the signaling elements that connect cell wall and membrane sensors with ion homeostasis and transport-mediated processes are largely unknown. Current research indicates that plant Integrin-Linked Kinases (ILKs), a subfamily Raf-like MAP2K Kinases, may have evolved to fulfill this role. In this review, we explore new findings on plant ILKs placing a particular focus on the connection between ILKs proteins unique structural features and ILKs functions. The ankyrin repeat motifs and the kinase domains of ILKs in Arabidopsis and land plants lineage, respectively, are analyzed and discussed as potential determinants of ILKs’ metal ion cofactor specificity and their enzymatic and interaction activities. Further, ILKs regulation through gene expression, subcellular localization, and ions and ion transporters is reviewed in the context of recent studies. Finally, using evidence from literature and interactomics databanks, we infer ILKs-dependent cellular pathways and highlight their potential in transmitting multiple types of signals originating at the interface between the cell wall and plasma membrane.